LEXICAL AND GRAMMATICAL DEVICES OF COHERENCE IN ENGLISH AND UZBEK PUBLICISTIC DISCOURSE (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2025)
This article investigates lexical and grammatical devices of coherence in English and Uzbek publicistic discourse. Based on a comparative analysis of contemporary media texts, the study identifies dominant cohesive mechanisms and examines their pragmatic and stylistic functions. The findings show that grammatical cohesion, particularly syntactic devices such as reduction, ellipsis, attachment, parcelling, and allusion, plays a leading role in ensuring textual coherence, while lexical devices support thematic continuity. Despite typological differences, both languages demonstrate similar coherence-building strategies influenced by linguistic and cultural factors.